Volumetric composition and shear strength evaluation of pultruded hybrid kenaf/glass fiber composites - Hashemi, Fariborz; Md Tahir, Paridah; Madsen, Bo; Jawaid, M; Majid, DL; Brancheriau, Loı¨c; AH, Juliana (SAGE Publications, 2015)
In the present study, six different combinations of pultruded hybrid kenaf/glass composites were fabricated. The number of kenaf and glass rovings was specifically selected to ensure constant local fiber volume fractions in the composites. The volumetric composition of the composites was determined by using a gravimetrically based method. Optical microscopy was used to determine the location of voids. The short-beam test method was used to determine the interlaminar shear strength of the composites, and the failure mode was observed. It was found that the void volume fraction of the composites was increased as a function of the kenaf fiber volume fraction. A linear relationship with high correlation (R2¼0.95) was established between the two volume fractions. Three types of voids were observed in the core region of the composites (lumen voids, interface voids and impregnation voids). The failure of the samples started with horizontal shear cracks that propagated into the core region, and ultimately the samples failed by a vertical crack. The interlaminar shear strength was found to decrease as a function of the hybrid fiber mixing ratio.